2020
DOI: 10.1088/1742-6596/1613/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences on students’ self-regulated learning in mathematics

Abstract: Self-regulated learning (SRL) is a process carried out by students on their awareness in formulating goals, determining strategies, motivating and monitoring themselves in learning and evaluating the results of their learning. This study aims to describe the SRL of junior high school students in learning mathematics from gender differences. The method used in this research is quantitative descriptive. The study was conducted at SMPN 1 Pecangaan. The sample used was 73 8th-grade students, consisting of 35 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…However, this research aligns with other studies that found no gender-based differentiation in academic procrastination (Astuti et al, 2021;Gohil, 2014). Some studies have suggested that females exhibit higher levels of self-regulation, a factor that predicts academic procrastination, compared to males (Liu et al, 2021;Rohman et al, 2020). Nevertheless, no significant difference in the level of selfregulated learning was observed between male and female students in this study.…”
contrasting
confidence: 84%
“…However, this research aligns with other studies that found no gender-based differentiation in academic procrastination (Astuti et al, 2021;Gohil, 2014). Some studies have suggested that females exhibit higher levels of self-regulation, a factor that predicts academic procrastination, compared to males (Liu et al, 2021;Rohman et al, 2020). Nevertheless, no significant difference in the level of selfregulated learning was observed between male and female students in this study.…”
contrasting
confidence: 84%
“…In a 9-week intervention with mathematics students in grade 4-6, it was found that there are positive effects from the use of rubrics in selfassessment and peer assessment on the students' self-efficacy and SRL behaviour (Granberg et al, 2021). Students who have strong levels of self-efficacy, self-attribution, and intrinsic task interest are motivated in SRL (Rohman et al, 2020).…”
Section: Emotion and Self-efficacy In Srlmentioning
confidence: 99%
“…Planning, goal-setting, organising, keeping track of oneself and self-evaluation at various stages throughout the acquisition process are all examples of SRL in the context of metacognitive processes. These procedures enable them to approach learning in a self-aware, informed, and aggressive manner (Rohman et al, 2020). Research demonstrates that students lack awareness of cognitive learning strategies, which limits the use of metacognition during self-study since students sometimes do not use the most effective study techniques (Alten et al, 2020).…”
Section: Metacognition In Srlmentioning
confidence: 99%
See 2 more Smart Citations